2010
DOI: 10.1007/s00421-010-1637-x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased variability in postural control strategies in young people with non-specific low back pain is associated with altered proprioceptive reweighting

Abstract: Optimal postural control is an essential capacity in daily life and can be highly variable. The purpose of this study was to investigate if young people have the ability to choose the optimal postural control strategy according to the postural condition and to investigate if non-specific low back pain (NSLBP) influences the variability in proprioceptive postural control strategies. Young individuals with NSLBP (n = 106) and healthy controls (n = 50) were tested on a force plate in different postural conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 152 publications
(180 citation statements)
references
References 42 publications
9
161
10
Order By: Relevance
“…Another study, with individuals with comparable moderate-to-high ODI scores after surgery, reported the need for 18 s after lumbar surgery but with vision (Kulig et al, 2009). Additionally, we found a comparable degree of down-weighting of lumbosacral proprioceptive signals and up-weighting of ankle proprioceptive signals in individuals with non-specific LBP without surgical history (Claeys et al, 2011), that affected STSTS performance (Claeys et al, 2012). Therefore, the current study suggests that the reliability of the lumbosacral proprioceptive signals still remains reduced after lumbar microdiscectomy.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Another study, with individuals with comparable moderate-to-high ODI scores after surgery, reported the need for 18 s after lumbar surgery but with vision (Kulig et al, 2009). Additionally, we found a comparable degree of down-weighting of lumbosacral proprioceptive signals and up-weighting of ankle proprioceptive signals in individuals with non-specific LBP without surgical history (Claeys et al, 2011), that affected STSTS performance (Claeys et al, 2012). Therefore, the current study suggests that the reliability of the lumbosacral proprioceptive signals still remains reduced after lumbar microdiscectomy.…”
Section: Discussionsupporting
confidence: 57%
“…1): transmuscular surgery + physiotherapy (n = 6), transmuscular surgery + usual care (n = 6), paramedian surgery + physiotherapy (n = 6), and paramedian surgery + usual care (n = 7). These groups were clustered by a mixed group design because power analysis (Brumagne et al, 2008;Claeys et al, 2011Claeys et al, , 2012Claeys et al, , 2015Janssens et al, 2015) revealed a sample size of 11 participants to provide adequate power (0.80 with a two-tailed alpha level of 0.05) to detect a clinically relevant difference in center of pressure displacement on unstable support surface (our primary outcome measure with smallest effect size). First, they were randomly allocated (blinded by computer algorithm) for surgical approach into a transmuscular group (n = 12; 7 women/5 men) and paramedian group (n = 13; 7 women/6 men).…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations